Spectroscopic analysis of cis-polyisoprene and polymethyl methacrylate graft copolymers - Wan Abdul Rahman, Wan Aizan (Faculty of Chemical & Natural Resources Engineering, 1990)
This paper explains the used of Fourier Transform Infra-Red Spectroscopy (FTIR) Nocolet MX-1 in analysing the PMMA content of the graft copolymer cis-polyisoprene/PMMA leading to its suspected mechanism. Both qualitative and quantitative applications were used.